2022
DOI: 10.1039/d2en00286h
|View full text |Cite
|
Sign up to set email alerts
|

Understanding trends in the mercury oxidation activity of single-atom catalysts

Abstract: Mercury pollutants emitted from coal-fired power plants are recognized as a global environmental problem. Rapid and sustainable catalytic oxidation of elemental mercury (Hg0) to oxidized mercury (Hg2+) is an essential...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 65 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…Yang et al 11,12 used a combined theoretical and experimental method to analyze the reaction mechanism of Fe SACs for the catalytic Hg 0 oxidation using O 2 ; they found that Fe SA /DV-N 4 has the highest catalytic activity, with an RDS energy barrier of 2.34 eV. Our previous study 13 predicted the catalytic activity of 3d, 4d, and 5d metal SACs (in the form of metal 1 −N 4 −C) for catalytic Hg 0 oxidation by the derived volcano activity plots; the results showed that Fe 1 −N 4 −C has the highest catalytic activity. However, it was found that the SACs catalyzed Hg 0 oxidations generally have high RDS energy barriers (>2 eV).…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al 11,12 used a combined theoretical and experimental method to analyze the reaction mechanism of Fe SACs for the catalytic Hg 0 oxidation using O 2 ; they found that Fe SA /DV-N 4 has the highest catalytic activity, with an RDS energy barrier of 2.34 eV. Our previous study 13 predicted the catalytic activity of 3d, 4d, and 5d metal SACs (in the form of metal 1 −N 4 −C) for catalytic Hg 0 oxidation by the derived volcano activity plots; the results showed that Fe 1 −N 4 −C has the highest catalytic activity. However, it was found that the SACs catalyzed Hg 0 oxidations generally have high RDS energy barriers (>2 eV).…”
Section: Introductionmentioning
confidence: 99%
“…Using the same modeling method as refs, ,, microkinetic modeling based on the previously mentioned kinetic parameters was carried out to further assess the catalyst activity in flue gas conditions. Herein, we selected temperature ( T ) and pressure ( P ) as the two descriptors and [log­(TOF)] as the reaction evaluator (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In this work, the process of oxidizing NO using H 2 O 2 over Fe–N 4 –C was studied by spin-polarized DFT calculations (ISPIN=2 of the VASP INCAR) with van der Waals corrections (DFT-D3). The reason for choosing Fe–N 4 –C as an example is that it is proven highly effective for both NO and Hg 0 oxidation using O 2 as the oxidant and can reach the theoretical optimal activity compared to other SACs. , First, we analyzed the adsorption properties of the *OH, *O, and *OOH species generated by *H 2 O 2 activation and other gas molecules (e.g., *NO) on the catalyst surface. After that, the catalytic oxidation of NO by *OH, *O, and *OOH on Fe–N 4 –C reaction pathways were thoroughly examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the seminal Sabatier principle, a good heterogeneous catalyst should neither bond to the adsorbate too strongly nor too weakly [110]. Therefore, almost all the derived heterogeneous catalytic models present a "volcano-shape" as a function of the key adsorbate binding energies (i.e., adsorption energies) of the reaction [111][112][113][114][115][116][117][118][119][120][121][122][123]. A catalytic volcano model allows people to derive the optimal activity of catalysis.…”
Section: Catalyst Design To Improve Activity and Target-product Selec...mentioning
confidence: 99%